Using Mind Maps to Distinguish Cultural Norms between French and United States Entrepreneurship Students. (5th February 2018) - Bandera, Cesar; Eminet, Aurélien; Passerini, Katia; Pon, Kevin
Abstract : The globalization of entrepreneurship education requires instructors to understand, and adjust the curriculum for, cultural disparities. This study investigates the impact of cultural norms on the attitudes of university entrepreneurship students in France and the United States—regions with contrasting Hofstede and Global Entrepreneurship Monitor indices. It uses mind maps from students as culturally agnostic open‐ended measures of their attitudes. Two mind maps were collected from each student, one on the appeal of entrepreneurship and one on the apprehension toward entrepreneurship, for a total of 1, 213 concepts that were then scored using the Moore–Bygrave staged model of entrepreneurship to measure student likes and dislikes toward innovation, the decision to launch a start‐up, new venture implementation, and venture growth. The Shannon entropy of a mind map was used as a measure of student fixation; lower entropy indicates the student is motivated or deterred by a subset of the curriculum, whereas higher entropy indicates that attitudinal components are more balanced across the curriculum. Participating students were enrolled in similar entrepreneurship courses, and exhibited attitudes with similar entropy. However, French students found the growth stage to be the most appealing and were most apprehensive about innovation, whereas U.S. students found innovation to be the most appealing stage and were most apprehensive about the growth stage, thus revealing different contextual drivers of learning and engagement with the educational materials. This research contributes to the advancement of entrepreneurship education in two ways. First, by using mind maps and differential model‐based semantic scoring, it distinguishes between motivation and deterrence, and accounts for both cognitive and affective components of attitudes toward entrepreneurship. Second, it presents a formative assessment technique with which educators can measure students' cultural disposition to the different topics of an entrepreneurship course, and can then tailor the syllabus to this disposition. This technique can potentially improve the effectiveness of entrepreneurship education in multicultural settings, such as those involving educators, students, or course material from different regions and cultures.